Demographic Variables and Their Impact on Organizational Trust - Amira Khaiat; Mohammed Lamine Slimane Tichtich (International Society of Philosophy and Cosmology, 2024)
This study explores the impact of demographic variables on organizational trust. It aims to present the concept of organizational trust and its dimensions, addressing its determinants, both personal and organizational. An analytical study was conducted involving a series of previous studies to display results and to examine the extent to which demographic determinants affect the organizational trust among employees at El Harrouch Hospital Institution. The study relied on the descriptive method and used surveys as a data collection tool. Significant statistical differences were found in the responses regarding organizational trust attributed to gender, with males showing higher levels of trust. There were also notable differences due to tenure, favoring those with over 20 years of service, and significant differences in trust attributed to job roles, favoring administrative staff.